Association between Polymorphism of β-Lactoglobulin Gene on Milk Yield and Quality in Local Sheep at Jonggol Animal Science Teaching and Research Unit (JASTRU) - Sumantri, Cece; D, Nurhayati; Farajallah, Ahmad; Anggraeni, A (ANNALES BOGORIENSES, 2008)
The aims of this study were to identify the effects polymorphism of β-lactoglobulin gene  on milk yield and percentage of milk protein  and  fat  in  local sheep. A total number of 83  heads of  lactating ewes  raised under an extensive management at  Jonggol Animal Science Teaching and Research Unit (JASTRU) of  the Faculty of Anima Science, Bogor Agricultural  University were  studied.  Research  activities  were  carried  out  through  some  step involving blood collection. DNA isolation, DNA amplification and separation of DNA fragments by electrophoresis with silver staining method. By using polymerase chain reaction (P  R) then genotyped by single strand  conformation polymorphism technique (SSCP), it was success fully amplified a fragment length at 420 bp in β-lactoglobulin gene located on  the exon 7. The electrophoresis  pattern  revealed 5 types of β-lactoglobulin gene and designated as AB. C, D and E types. The proportion for  those respective 5 type from the  highest to  the lowest were for A (27.7%)C (16.87%), D (12.05%), (10.84%) and B (9.64%)  respectively. There were no  significant effect  polymorphism β-lactoglobulin gene on both milk yield and quality  in  I  cal  sheep at JASTRU.   Keywords : polymorphism. β-lactoglobulin in gene, PCR-SSCP and local sheep